2012
DOI: 10.1124/dmd.112.045625
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a Specific Monoclonal Antibody against Human UDP-Glucuronosyltransferase (UGT) 1A9 and Evaluation of UGT1A9 Protein Levels in Human Tissues

Abstract: ABSTRACT:Glucuronidation is a major detoxification pathway of drugs and xenobiotics that are catalyzed by the UDP-glucuronosyltransferase (UGT) superfamily. Determination of the protein levels of the individual UGT isoforms in human tissues is required for the successful extrapolation of in vitro metabolic data to in vivo clearance. Most previous studies evaluating UGT isoform expression were limited to the mRNA level because of the high degree of amino acid sequence homology between UGT isoforms that has hamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 37 publications
5
22
0
Order By: Relevance
“…It has been reported previously that UGT1A mRNA and protein levels do not always correlate with each other. [24][25][26] Similar to the reports, an unexplained epigenetic mechanism of post-transcriptional regulation of Ugt1a6 and Ugt1a7 may also exist in rat brains.…”
Section: Fig 3 Changes In Ahr Mrna Expression By Bnf In Rat Brainssupporting
confidence: 83%
“…It has been reported previously that UGT1A mRNA and protein levels do not always correlate with each other. [24][25][26] Similar to the reports, an unexplained epigenetic mechanism of post-transcriptional regulation of Ugt1a6 and Ugt1a7 may also exist in rat brains.…”
Section: Fig 3 Changes In Ahr Mrna Expression By Bnf In Rat Brainssupporting
confidence: 83%
“…However, the increase in APAP glucuronidation was not correlated with the increase in Ugt1a6 and Ugt1a7 mRNA expression levels in the striatum. A previous report showed that human UGT1A mRNA and protein levels did not always correlate with each other (Izukawa et al, 2009;Oda et al, 2012;Ohtsuki et al, 2012), suggesting that the level of induction of Ugt mRNA does not correlate with the induction of glucuronidation activities. To determine changes in Ugt1a6 and Ugt1a7 enzyme activities in detail may require more specific Ugt1a6 and Ugt1a7 substrates.…”
Section: Discussionmentioning
confidence: 89%
“…Recent gene expression studies identified a number of transferases in the human skin ( Table 1), enzymes that are important for metabolic elimination and detoxification. Although useful for approximating the protein levels, studies of mRNA expression are often limited by poor correlation between measured mRNA levels and actual protein levels (Izukawa et al, 2009;Maier et al, 2009;Oda et al, 2012;Vogel and Marcotte, 2012). Proteomic profiling may solve this problem, but a recent large study failed to detect UGTs and NATs in whole human skin (van Eijl et al, 2012), despite previous reports of their activities (Table 2).…”
Section: Discussionmentioning
confidence: 99%